TECHNICAL EFFICIENCY OF SEED POTATO FARMERS OF BADAKSHAN PROVINCE OF AFGHANISTAN - Srinivas, T; Rizvi, SJH; Aw-Hassan, A; Manan, A R; Kadian, M s (Potato Journal, 2013)
Potato is the second staple food after wheat in Afghanistan. International Centre for Agricultural Research in the Dry Areas (ICARDA) and International Potato Centre (CIP) introduced high yielding potato variety Kufri Chandramukhi (KCM) and its production technology to develop an efficient seed production system that helped in reducing poverty and increasing food production in Bahrak district of Badakhshan province of Afghanistan. Purposive and multistage sampling technique was used for selecting the sample seed potato farmers for the present study. The economic benefits and technical efficiency levels of farmers were estimated using the data collected from the participating and non-participating farmers in the intervention. A high degree of inefficiency (76%) in the production of seed potato was observed indicating that there is scope for farmers to increase the potato production by 76% just by way of realizing technical efficiency. As the efficiency levels are low, efforts to improve technical efficiency and correct adoption of seed potato production technology would be more productive and cost effective through more trainings, field days, etc.